Identification of Proteins Bound to Dengue Viral RNA In Vivo Reveals New Host Proteins Important for Virus Replication - Stacia L. Phillips (American Society for Microbiology, 2016)
ABSTRACT Dengue virus is the most prevalent cause of arthropod-borne infection worldwide. Due to the limited coding capacity of the viral genome and the complexity of the viral life cycle, host cell proteins play essential roles throughout the course of viral infection. Host RNA-binding proteins mediate various aspects of virus replication through their physical interactions with viral RNA. Here we describe a technique designed to identify such interactions in the context of infected cells using UV cross-linking followed by antisense-mediated affinity purification and mass spectrometry. Using this approach, we identified interactions, several of them novel, between host proteins and dengue viral RNA in infected Huh7 cells. Most of these interactions were subsequently validated using RNA immunoprecipitation. Using small interfering RNA (siRNA)-mediated gene silencing, we showed that more than half of these host proteins are likely involved in regulating virus replication, demonstrating the utility of this method in identifying biologically relevant interactions that may not be identified using traditional in vitro approaches. IMPORTANCE Dengue virus is the most prevalent cause of arthropod-borne infection worldwide. Viral RNA molecules physically interact with cellular RNA-binding proteins (RBPs) throughout the course of infection; the identification of such interactions will lead to the elucidation of the molecular mechanisms of virus replication. Until now, the identification of host proteins bound to dengue viral RNA has been accomplished using in vitro strategies. Here, we used a method for the specific purification of dengue viral ribonucleoprotein (RNP) complexes from infected cells and subsequently identified the associated proteins by mass spectrometry. We then validated a functional role for the majority of these proteins in mediating efficient virus replication. This approach has broad relevance to virology and RNA biology, as it could theoretically be used to purify any viral RNP complex of interest.